Association of arterial stiffness with aortic calcification and tortuosity. Issue 33 (August 2019) - Moon, Inki; Jin, Kwang Nam; Kim, Hack-Lyoung; Suh, Hyeon Jeong; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Zo, Joo-Hee; Kim, Myung-A
Abstract : Abstract: Impact of arterial stiffness on aortic morphology has not been well evaluated. We sought to investigate the association of brachial-ankle pulse wave velocity (baPWV) with aortic calcification and tortuosity. A total of 181 patients (65.4 ± 10.4 years, males 59.7%) who underwent computed tomographic angiography and baPWV measurement within 1 month of study entry were retrospectively reviewed. Aortic calcification was quantified by the calcium scoring software system. Aortic tortuosity was defined as the length of the midline in the aorta divided by the length of linear line from the aortic root to the distal end of the thoraco-abdominal aorta. In simple correlation analyses, baPWV was correlated with aortic calcification ( r  = 0.36, P  < .001) and tortuosity ( r  = 0.16, P  = .030). However, these significances disappeared after controlling for confounders in multivariate analyses. Factors showing an independent association with aortic calcification were age ( β  = 0.37, P  < .001), hypertension ( β  = 0.19, P  = .003), diabetes mellitus ( β  = 0.12, P  = .045), smoking ( β  = 0.17, P  = .016), and estimated glomerular filtration rate ( β  = –0.25, P  = .002). Factors showing an independent association with aortic tortuosity were age ( β  = 0.34, P  < .001), body mass index ( β  = –0.19, P  = .018), and diabetes mellitus ( β  = –0.21, P  = .003). In conclusion, baPWV reflecting arterial stiffness was not associated with aortic calcification and tortuosity. Traditional cardiovascular risk factors were more influential to aortic geometry. Further studies with a larger sample size are needed to confirm our results.